1999
DOI: 10.1046/j.1570-7458.1999.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of two parasitoid wasps to nectar odors as a function of experience

Abstract: Adult parasitoid wasps can learn to recognize specific resource‐based cues, making them adept at locating essential resources within their native habitats. However, relatively little is known about their ability to recognize the odors emitted by flowers and extra‐floral nectar glands. A novel test arena mimicking the distribution of nectaries within an umbelliferous inflorescence was developed to measure and compare the responses of two eulophid wasps, Edovum puttleri and Pediobius foveolatus, to nectar‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
(55 reference statements)
1
29
0
Order By: Relevance
“…This is less than 10% of the time she needs to ingest a full nectar meal on a honey source with similar sugar concentration (Siekmann et al, 2001). The time needed to gain experience is in the same order of magnitude as published elsewhere (Lewis and Takasu, 1990;Lewis, 1993, 1996;Patt et al, 1999). Straight after the brief feeding experience, wasps experienced the scent of the flowers for an additional 20 s. This was achieved by holding the wasp close to the flowers without allowing her to climb onto them.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…This is less than 10% of the time she needs to ingest a full nectar meal on a honey source with similar sugar concentration (Siekmann et al, 2001). The time needed to gain experience is in the same order of magnitude as published elsewhere (Lewis and Takasu, 1990;Lewis, 1993, 1996;Patt et al, 1999). Straight after the brief feeding experience, wasps experienced the scent of the flowers for an additional 20 s. This was achieved by holding the wasp close to the flowers without allowing her to climb onto them.…”
Section: Methodsmentioning
confidence: 66%
“…Parasitic wasps use olfaction to locate nectar sources (Leius, 1967;Lewis and Takasu, 1990;Wäckers and Lewis, 1994;Patt et al, 1999) and to some degree visual cues (Wäckers, 1994). There are only a few studies on how parasitic wasps locate potential nectar sources in the presence of hosts.…”
Section: Introductionmentioning
confidence: 99%
“…However, Patt et al (1999) demonstrated that eulophid parasitoid wasps learn to find and feed from artificial flowers more effectively when they include honey water or Foeniculum nectar than when sugar solutions are used, providing behavioral data suggestive of nectar scent in this system. The sampling methodology was suitable for strongly scented flowers with tubular corollas or spurs and large nectar volumes.…”
Section: Are Floral Nectars Scented? Indirect Evidence From the Litermentioning
confidence: 98%
“…The gradient in solute concentration occurring within a nectar drop (Heracleum mantegazzianum; Corbet et al, 1979) may play an important role in these events. Recently, two species of parasitoid wasps have been shown to respond to odors from nectaries of dill (Patt, Hamilton, and Lashomb, 1999). Although nectaries of the Apiaceae themselves may exhibit distinctive colors (Behrens, 1879), unlike caraway the nectaries even may change hue with floret phenology, as in Anethum graveolens (Szujkó-Lacza, 1971).…”
Section: Floral Nectar Yields Among Umbel Orders and Individual Plants-mentioning
confidence: 99%